Departamento de Materiais Odontológicos e Prótese - Dekon, Stefan Fiuza de Carvalho; Zavanelli, Adriana Cristina; Santos, Daniela Micheline dos; Barbosa, Débora de Barros; Rocha, Eduardo Passos; Pellizzer, Eduardo Piza; Verri, Fellippo Ramos; Gennari Filho, Humberto; Mazaro, José Vitor Quinelli; Goiato, Marcelo Coelho; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Stefan Fiuza de Carvalho Dekon